Combined analysis of the transcriptome and metabolome provides insights into the fleshy stem expansion mechanism in stem lettuce - Huang, Ying; Li, Yanwen; Liu, Zhenning; Chen, Wanqin; Wang, Yalin; Wang, Xiaohua; Liu, Yihua; Zheng, Yangxia (Frontiers in Plant Science, 2022)
As a stem variety of lettuce, the fleshy stem is the main product organ of stem lettuce. The molecular mechanism of fleshy stem expansion in stem lettuce is a complex biological process. In the study, the material accumulation, gene expression, and morphogenesis during fleshy stem expansion process were analyzed by the comparative analysis of metabolome, transcriptome and the anatomical studies. The anatomical studies showed that the occurrence and activity of vascular cambium mainly led to the development of fleshy stems; and the volume of pith cells gradually increased and arranged tightly during the expansion process. A total of 822 differential metabolites and 9,383 differentially expressed genes (DEGs) were identified by the metabolomics and transcriptomics analyses, respectively. These changes significantly enriched in sugar synthesis, glycolysis, and plant hormone anabolism. The expression profiles of genes in the sugar metabolic pathway gradually increased in fleshy stem expansion process. But the sucrose content was the highest in the early stage of fleshy stem expansion, other sugars such as fructose and glucose content increased during fleshy stem expansion process. Plant hormones, including IAA, GA, CTK, and JA, depicted important roles at different stem expansion stages. A total of 1,805 DEGs were identified as transcription factors, such as MYB, bHLH, and bZIP, indicating that these transcription factor families might regulate the fleshy stems expansion in lettuce. In addition, the expression patterns identified by qRT-PCR were consistent with the expression abundance identified by the transcriptome data. The important genes and metabolites identified in the lettuce fleshy stem expansion process will provide important information for the further molecular mechanism study of lettuce fleshy stem growth and development.